Nutrient removal in floating wetland using different plant species (Eleocheris variegate (Poir.) C. Presl, Scirpus mucronatus L. and Phylidrum lanuginosum Banks ex Gaertn) and floating mat coverage - Ibrahim, Muhammad Sanusi (2017)
Nutrients such as ammonia, nitrate, nitrite and phosphorus are the common contaminants discharged into the water bodies. Most of Malaysian wetlands were polluted through nutrient discharge from agricultural runoff and anthropogenic activities. Studies on floating treatment wetland efficiency using native plant species to reduce the nutrient were lacking in Malaysia. The potential of floating treatment wetland in water purification using three plant species of Spike rush (Eleocheris variegata), Bug bulrush(Scirpus mucronatus) and Fan grass (Phylidrum lanuginosum), and floating mat coverage as well as plant species combinations was examined. The result showed the plant species performed better in ammonia, nitrate and phosphorous removal. Spike rush exhibited significantly higher ammonia-nitrogen removal in high nutrient concentration water (p = 0.013) compared to low nutrient concentration water. While in nitrate, the plant exhibited significantly higher removal in low nutrient concentration water (p = 0.000) compared to high nutrient concentration water. Similarly, the plant showed significantly higher phosphorus removal in low nutrient concentration water (p = 0.000) compared to high nutrient concentration water. However, Bug bulrush was also exhibited significantly higher ammonia- nitrogen removal in higher nutrient concentration water (p = 0.021) compared to low nutrient concentration water. Conversely, the plant showed significantly higher nitrate removal in low nutrient concentration water (p = 0.000) compared to high. Similarly, the plant exhibited significantly higher phosphorus removal in low nutrient concentration water (p = 0.000) compared to high. However, Fan grass exhibited significantly higher ammonia- nitrogen removal in low nutrient concentration water (p = 0.021) compared to high nutrient concentration water. While, in nitrate removal, the plant showed higher in high nutrient concentration water (p = 0.000) compared to low nutrient concentration water. Similarly, the plant exhibited significantly higher phosphorous removal in high nutrient concentration (p = 0.000) compared to low nutrient concentration. In BOD removal, the result showed only significant differences in low nutrient concentration water between the plant species (p = 0.046). However, The result showed no significance differences in nutrient removal between the floating mat coverage, except for nitrate in 20% floating mat coverage which showed significantly higher removal (p = 0.031) compared to 60% floating mat coverage. Furthermore, the result showed two plant species in 60% floating mat coverage was significantly higher in nitrate removal (p = 0.041) compared to control. However, three plant species showed significantly higher phosphorus removal (p = 0.006) compared to two plant species and control. Moreover, the control of 40% floating mat coverage exhibited significantly higher Biochemical oxygen demand removal (p = 0.001) compared to three and two plant species combinations.